2005
DOI: 10.1103/physreva.72.023401
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of atomic polarization in paraffin-coated cesium vapor cells

Abstract: The relaxation of atomic polarization in buffer-gas-free, paraffin-coated cesium vapor cells is studied using a variation on Franzen's technique of "relaxation in the dark" [Franzen, Phys. Rev. 115, 850 (1959)]. In the present experiment, narrow-band, circularly polarized pump light, resonant with the Cs D2 transition, orients atoms along a longitudinal magnetic field, and time-dependent optical rotation of linearly polarized probe light is measured to determine the relaxation rates of the atomic orientation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 51 publications
5
78
0
1
Order By: Relevance
“…2,5,53 It has been observed 54,55 that alkali vapor density increases significantly when a paraffin-coated cell is exposed to light (particularly uv and near-uv light) due to the lightinduced atomic desorption (LIAD) effect, 56 which causes absorbed atoms to be ejected from the paraffin coating. Recently, LIAD effects on alkali spin relaxation have been investigated, 6 with a focus on non-thermal control of alkali vapor density. 57 The exact mechanisms of LIAD in paraffin are not yet understood; however, it is clear that a combination of surface processes and light-enhanced diffusion of alkali atoms within the bulk of the coating are important.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,53 It has been observed 54,55 that alkali vapor density increases significantly when a paraffin-coated cell is exposed to light (particularly uv and near-uv light) due to the lightinduced atomic desorption (LIAD) effect, 56 which causes absorbed atoms to be ejected from the paraffin coating. Recently, LIAD effects on alkali spin relaxation have been investigated, 6 with a focus on non-thermal control of alkali vapor density. 57 The exact mechanisms of LIAD in paraffin are not yet understood; however, it is clear that a combination of surface processes and light-enhanced diffusion of alkali atoms within the bulk of the coating are important.…”
Section: Introductionmentioning
confidence: 99%
“…The authors applied LIAD and observed no significant change in the spin relaxation rate beyond what was expected from the faster rate of the spin-exchange collisions due to the density growth [61].…”
Section: Liad For Atomic Spectroscopymentioning
confidence: 99%
“…The fibers are loaded with natural Rb vapor for a period of 3.5 weeks. At the end of the vapor loading process the current source to the Rb getter is switched off to minimize the influence of the Rb source on the relaxation time measurement [19]. During the data collection, the Rb vapor density was measured and was found to remain steady over the corresponding time period.…”
mentioning
confidence: 99%
“…The Zeeman sub-level degeneracy is lifted by applying a dc magnetic field (≤3.5 mT) along the guidance axis of the optical fibers using a solenoid wound around the vacuum chamber. The electron spin randomization rate 1 was measured using a variation of Franzen technique [19]. This consists of abruptly shutting off the pump beam with a chopper at 70 Hz frequency rate, and detecting during this pump "dark time", the exponentially decaying atom polarization by recording the polarization rotation, , of a linearly polarized weak probe beam at the fiber output.…”
mentioning
confidence: 99%